Knockdown of SFRS9 Inhibits Progression of Colorectal Cancer Through Triggering Ferroptosis Mediated by GPX4 Reduction - Wang, Rui; Xing, Rui; Su, Qi; Yin, Hongzhuan; Wu, Di; Lv, Chi; Yan, Zhaopeng (Frontiers in Oncology, 2021)
Ferroptosis, a newly discovered form of programmed cell death characterized by lipid peroxidation, crafts a new perspective on cancer treatment. Serine and arginine rich splicing factor 9 (SFRS9) is frequently described as a proto-oncogene in cervical and bladder cancer. However, it is largely unknown the role of SFRS9 in colorectal cancer (CRC) and whether SFRS9 exerts its function associated with ferroptosis. Herein, we found that the expression of SFRS9 mRNA and protein in the CRC tissues was obviously higher than that in the paracancerous tissues. Function assays revealed that SFRS9 overexpression (SFRS9-OE) significantly promoted cell viability, cell cycle progression and colony formation of CRC cells. While SFRS9 knockdown by shRNAs transfection inhibited these progressions. Furthermore, cell death and lipid peroxidation induced by ferroptosis inducers erastin and sorafenib were suppressed by SFRS9-OE. Bioinformatics analysis indicates that SFRS9 can binding to peroxidase 4 (GPX4) mRNA which is a central regulator of ferroptosis. Western blot showed that GPX4 protein expression was clearly elevated upon SFRS9-OE, while it was decreased in SFRS9-inhibited CRC cells. RNA immunoprecipitation experiment was carried out in HCT116 cells to confirm the binding of SFRS9 and GPX4 mRNA specifically. SiGPX4 transfection reversed the inhibitory effects of SFRS9-OE on the erastin and sorafenib-induced ferroptosis. Consistent with our in vitro observations, SFRS9 promoted the growth of tumors while SFRS9 knockdown significantly inhibited tumor growth in nude mice. In conclusion, SFRS9 represents an obstructive factor to ferroptosis by upregulating GPX4 protein expression, and knocking down SFRS9 might be an effective treatment for CRC.